BENTUK DIPLOMASI BUDAYA INDONESIA PADA FESTIVAL SAMOSIR MUSIC INTERNASIONAL 2018-2023 - Siagian, Cristin Arti Kasih; Pahlawan, Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Indonesia's cultural diplomacy at the International Samosir Music Festival (FSMI) shows the important role of culture in deepening relations between nations. This research aims to analyze in more depth the forms of Indonesian cultural diplomacy revealed through FSMI, with an emphasis on efforts to promote Indonesian cultural diversity, namely Traditional Batak music and improve the quality of diplomatic relations between Indonesia and participating countries. This research was conducted using a qualitative method with a descriptive approach and using secondary data collection techniques obtained through literature study, in this case through book sources, journal articles, research papers, working papers, official online data bases or archives and interviews with the leadership of the Samosir Music Festival. International. The author uses a constructivist perspective with a country level of analysis. The author analyzes the research results using cultural diplomacy theory to explain the form of diplomacy that Indonesia has carried out through an international music festival. The results of the research conducted show that the Indonesian people and even foreign tourists who come are very interested in Indonesian culture, especially Traditional Batak art since the International Samosir Music Festival was held in Samosir, North Sumatra. The research results prove that the cultural diplomacy carried out by Indonesia is fulfilled as evidenced by several activities carried out, and has had a positive impact on the various countries that come and collaborate in it. Keywords: Samosir Music International Festival (FSMI), cultural diplomacy, Traditional Batak Arts.